Volatile constituents of the resins from protium subserratum (engl.) engl. And tetragastris panamensis (engl.) kuntz - Zoghbi, Maria das Graças Bichara; Andrade, Eloísa Helena de Aguiar; Santos, Alberdan Silva; Luz, Arnaldo Iran R.; Maia, José Guilherme Soares (Journal of Essential Oil Research, 1998)
The hexane extracts of resins from Protium subserratum and Tetragastris panamensis were analyzed by GC/MS. The main constituents found in the extract obtained from the resin of P. subserratum were β-phellandrene (56.3%) and α-phellandrene (20.8%). The most abundant components identified in the extract obtained from the resin of T. panamensis were β-caryophyllene (27.5%) and α-pinene (6.7%). © 1998, Taylor & Francis Group, LLC. All rights reserved.